How Does Long-Term Orientation Influence the Investments of Venture Capitals? Evidence From the Organizational Level - Zheng, Tianyi (Frontiers in Psychology, 2022)
Amid great uncertainty along with the possibility of huge returns, venture investment decisions are both technical and artistic. Past studies have paid much attention to the influences of objective factors on venture investment. However, the subjective factors have been relatively ignored. As a salient psychological mechanism, temporal focus is of great importance for venture capitalists when making their investment decisions. This study used content analysis to investigate how the temporal focus at the organizational level affects the investment decisions of venture capital firms. The results revealed that VCs with a higher level of long-term orientation prefer to invest in less popular industries and ventures in the expansion period. Meanwhile, they are less likely to invest in very new start-ups. Moreover, long-term oriented VCs tend to re-invest start-ups in their portfolios instead of just shooting once on numerous single start-ups. However, I did not find any support about VC’s preferences for ventures with a high level of human capital.